2016
DOI: 10.1038/srep37652
|View full text |Cite
|
Sign up to set email alerts
|

TWIST1 drives cisplatin resistance and cell survival in an ovarian cancer model, via upregulation of GAS6, L1CAM, and Akt signalling

Abstract: Epithelial ovarian cancer (EOC) is the most deadly gynaecologic malignancy due to late onset of symptoms and propensity towards drug resistance. Epithelial-mesenchymal transition (EMT) has been linked to the development of chemoresistance in other cancers, yet little is known regarding its role in EOC. In this study, we sought to determine the role of the transcription factor TWIST1, a master regulator of EMT, on cisplatin resistance in an EOC model. We created two Ovcar8-derived cell lines that differed only … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
57
0
1

Year Published

2017
2017
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 68 publications
(65 citation statements)
references
References 61 publications
7
57
0
1
Order By: Relevance
“…Collectively, these data demonstrated that TW‐dependent growth of U87MG cells in vivo was associated with activation of AKT. In other cancers, TW regulates AKT signaling through phospho‐activation (Li and Zhou, ) (Roberts et al ., ) as well as transcriptional upregulation (Cheng et al ., ). Here, TW deletion did not alter AKT gene expression (not shown), and therefore, in U87MG TW appears to primarily regulate AKT signaling through phosphorylation.…”
Section: Resultsmentioning
confidence: 99%
“…Collectively, these data demonstrated that TW‐dependent growth of U87MG cells in vivo was associated with activation of AKT. In other cancers, TW regulates AKT signaling through phospho‐activation (Li and Zhou, ) (Roberts et al ., ) as well as transcriptional upregulation (Cheng et al ., ). Here, TW deletion did not alter AKT gene expression (not shown), and therefore, in U87MG TW appears to primarily regulate AKT signaling through phosphorylation.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have demonstrated that the Gas6/Axl is involved in chemoresistance in breast cancer and indicated that the inactivation of the Gas6/Axl pathway may contribute to the activity of chemotherapeutic drugs (35,36). Recent studies have demonstrated that the inhibition of the Gas6/Axl pathway improved the efficacy of chemotherapies in preclinical models of advanced pancreatic and ovarian cancer (37).…”
Section: Discussionmentioning
confidence: 99%
“…RNA sequencing analysis revealed that TWIST1 expression resulted in upregulation of GAS6 and the activation of the AKT pathway. On the other side, knockdown studies demonstrated that the loss of GAS6 sensitized these cells to cisplatin treatment and suggest a potential mechanism of drug resistance in EOC (Roberts et al, 2016). Lee et al could show that GAS6 regulates the cell cycle and apoptosis of prostate cancer (PCa) cells in response to docetaxel chemotherapy.…”
Section: Introductionmentioning
confidence: 99%